To solve the equation \( 25^{3x+1} = 5^{x-6} \), let's first express everything in terms of the same base.
Since \( 25 \) can be written as \( 5^2 \), we have:
\[ 25^{3x+1} = (5^2)^{3x+1} = 5^{2(3x+1)} = 5^{6x + 2} \]
Now substituting back into the original equation gives us:
\[ 5^{6x + 2} = 5^{x - 6} \]
Since the bases are the same, we can set the exponents equal to each other:
\[ 6x + 2 = x - 6 \]
Now, we will solve for \( x \):
- Subtract \( x \) from both sides:
\[ 6x - x + 2 = -6 \]
This simplifies to:
\[ 5x + 2 = -6 \]
- Next, subtract \( 2 \) from both sides:
\[ 5x = -6 - 2 \]
This results in:
\[ 5x = -8 \]
- Now, divide by \( 5 \):
\[ x = -\frac{8}{5} \]
Thus, the solution is:
\[ x = -\frac{8}{5} \]
The answer corresponds to option D:
D \(x = -\frac{8}{5}\).